REPRESENTASI SEMI-KONKRIT DALAM MENUMBUHKAN PEMAHAMAN KONSEP PECAHAN - PUJI RAHMAWATI (Bestari: Jurnal Pendidikan dan Kebudayaan, 2022)
This study aims to determine whether the response can affect the understanding of the concept of fractions (regular and mixed) students of class VII MTs. Istiqomah Entikong. The type of research used is a quantitative approach with the type of research being experimental, using Pre-Experimental Designs (Nondesigns) with a design type, namely One-Group Pretest-Posttest Design which is only carried out in one group without any comparison group.Sourced from the average pretest result was 67.722 and posttest was 79.11. Based on calculations using the t test, it is obtained that t count 0.168 is more than t table 1.859, Ha is accepted and H¬O is rejected, meaning that this research shows that response is able to influence and foster understanding of the concept of fractions.